Winning megadeals: The dual role of acquirer advisors in loan-financed mergers and acquisitions - Chen, Chong; Wu, Xueping (Journal of Corporate Finance, 2021)
Acquirer advisors now often arrange syndicated loans financing merger and acquisition deals they advise on. This paper shows that such an advisor-lender dual role facilitates valuable big-ticket deals. There is a positive announcement effect for the acquirer which also shows no systematic post-deal underperformance—dispelling concerns about the advisor abetting managerial empire building. But advisor-led syndicated loans, despite being larger in size, have higher loan spreads than those led by non-advisors. Advisors apparently have an information advantage but rent extraction is unlikely. The higher charges are justifiable in view of the significantly lower post-deal creditworthiness of dual-role bidders. Advisor-lender's superior information about adverse changes in the credit risk is rationally priced into the dual-role interest rate premium.